2018
DOI: 10.1002/adma.201802440
|View full text |Cite
|
Sign up to set email alerts
|

DNA Nanotweezers and Graphene Transistor Enable Label‐Free Genotyping

Abstract: Electronic DNA‐biosensor with a single nucleotide resolution capability is highly desirable for personalized medicine. However, existing DNA‐biosensors, especially single nucleotide polymorphism (SNP) detection systems, have poor sensitivity and specificity and lack real‐time wireless data transmission. DNA‐tweezers with graphene field effect transistor (FET) are used for SNP detection and data are transmitted wirelessly for analysis. Picomolar sensitivity of quantitative SNP detection is achieved by observing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 39 publications
1
74
0
1
Order By: Relevance
“…We then examined electrical sensing of DNA in fluid. Consistent with prior reports 5,14 , we also observed that the physical contact of ssDNA strands (let-7b sequence, Supplementary Table 2) imposed n-type doping effects on flat graphene, resulting in a negative shift of Dirac point as shown in Fig. 2a-c.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We then examined electrical sensing of DNA in fluid. Consistent with prior reports 5,14 , we also observed that the physical contact of ssDNA strands (let-7b sequence, Supplementary Table 2) imposed n-type doping effects on flat graphene, resulting in a negative shift of Dirac point as shown in Fig. 2a-c.…”
Section: Resultssupporting
confidence: 91%
“…8. and Supplementary Table 2) 5,14 . To verify that the DNA molecules were immobilized on the graphene, the surfaces of flat and crumpled graphene were probed using an AFM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we dissolved the PBASE powder in DMSO to make the binder we need. 100 mM ethanolamine was used to deactivate the excess reactive groups of PBASE to prevent possible nonspecific binding events, then it was rinsed by DI water [31][32][33]. The prepared PBASE was uniformly applied to the sensor D-type region at ambient temperature, and it was allowed to stand for 4 h while waiting for PBASE to bond with the graphene of the D-type region.…”
Section: The Specific Detection Of Biosensormentioning
confidence: 99%
“…B) DNA tweezers probe design. Adapted with permission . Copyright 2018, Wiley‐VCH Verlag GmbH &Co. KGaA, Weinheim.…”
Section: Dna Nanomachinesmentioning
confidence: 99%